Combinations of Freeze-Dried Amorphous Vardenafil Hydrochloride with Saccharides as a Way to Enhance Dissolution Rate and Permeability - Gabriela Wiergowska; Dominika Ludowicz; Kamil Wdowiak; Andrzej Miklaszewski; Kornelia Lewandowska; Judyta Cielecka-Piontek (Pharmaceuticals, 2021)
To improve physicochemical properties of vardenafil hydrochloride (VAR), its amorphous form and combinations with excipients—hydroxypropyl methylcellulose (HPMC) and β-cyclodextrin (β-CD)—were prepared. The impact of the modification on physicochemical properties was estimated by comparing amorphous mixtures of VAR to their crystalline form. The amorphous form of VAR was obtained as a result of the freeze-drying process. Confirmation of the identity of the amorphous dispersion of VAR was obtained through the use of comprehensive analysis techniques—X-ray powder diffraction (PXRD) and differential scanning calorimetry (DSC), supported by FT-IR (Fourier-transform infrared spectroscopy) coupled with density functional theory (DFT) calculations. The amorphous mixtures of VAR increased its apparent solubility compared to the crystalline form. Moreover, a nearly 1.3-fold increase of amorphous VAR permeability through membranes simulating gastrointestinal epithelium as a consequence of the changes of apparent solubility (Papp crystalline VAR = 6.83 × 10−6 cm/s vs. Papp amorphous VAR = 8.75 × 10−6 cm/s) was observed, especially for its combinations with β-CD in the ratio of 1:5—more than 1.5-fold increase (Papp amorphous VAR = 8.75 × 10−6 cm/s vs. Papp amorphous VAR:β-CD 1:5 = 13.43 × 10−6 cm/s). The stability of the amorphous VAR was confirmed for 7 months. The HPMC and β-CD are effective modifiers of its apparent solubility and permeation through membranes simulating gastrointestinal epithelium, suggesting a possibility of a stronger pharmacological effect.